In vivo multiplexed OPT and FLIM OPT of an adult zebrafish cancer disease model - Kumar,S; Lockwood,N; Ramel,MC; Correia,T; Ellis,M; Alexandrov,Y; Andrews,N; Patel,R; Bugeon,L; Dallman,MJ; Brandner,S; Arridge,S; et al. (2016)
We report angular multiplexed OPT and FLIM OPT applied to in vivo imaging of cancer and FRET biosensors in adult zebrafish. Multiple-spectral 3-D datasets of entire adult zebrafish can be acquired in 3 minutes.